High-throughput RNA sequencing reveals structural differences of orthologous brain-expressed genes between western lowland gorillas and humans - Lipovich, Leonard (J Comp Neurol, 2015)
The human brain, and human cognitive abilities, are strikingly different from those of other great apes despite relatively modest genome sequence divergence. However, little is presently known about the interspecies divergence in gene structure and transcription that might contribute to these phenotypic differences. To date, most comparative studies of gene structure in the brain have examined humans, chimpanzees, and macaque monkeys. To add to this body of knowledge, we analyze here the brain transcriptome of the western lowland gorilla (Gorilla gorilla gorilla), an African great ape species that is phylogenetically closely related to humans, but with a brain that is approximately one-third the size. Manual transcriptome curation from a sample of the planum temporale region of the neocortex revealed 12 protein-coding genes and one noncoding-RNA gene with exons in the gorilla unmatched by public transcriptome data from the orthologous human loci. These interspecies gene structure differences accounted for a total of 134 amino acids in proteins found in the gorilla that were absent from protein products of the orthologous human genes. Proteins varying in structure between human and gorilla were involved in immunity and energy metabolism, suggesting their relevance to phenotypic differences. This gorilla neocortical transcriptome comprises an empirical, not homology- or prediction-driven, resource for orthologous gene comparisons between human and gorilla. These findings provide a unique repository of the sequences and structures of thousands of genes transcribed in the gorilla brain, pointing to candidate genes that may contribute to the traits distinguishing humans from other closely related great apes. Using next-generation RNA sequencing of a Gorilla planum temporale (red dot), with transcript-togenome alignments, the authors demonstrate different sequences of orthologous human and gorilla brain messenger RNA and protein molecules. These distinctions relate to the genomic basis of phenotypic differences among hominids, heralding a new era of comparative molecular morphology.